Weak backbone CH⋯OC and side chain tBu⋯tBu London interactions help promote helix folding of achiral NtBu peptoids. Issue 24 (4th March 2016) - Angelici, G.; Bhattacharjee, N.; Roy, O.; Faure, S.; Didierjean, C.; Jouffret, L.; Jolibois, F.; Perrin, L.; Taillefumier, C.
Abstract : The synthesis and helix folding propensity of achiral all- cis amide (N t Bu)-glycine oligomers is reported. Abstract : The synthesis of all- cis amide (N t Bu)-glycine oligomers up to 15 residues long by a blockwise coupling approach is reported. The structure and dynamical behavior of these peptoids have been studied by X-ray crystallography, NMR and molecular modeling. Analyses reveal that the folding of these oligomers is driven by weak CH⋯OC hydrogen bonding along the peptoid backbone and London interaction between t Bu⋯ t Bu side-chains.